The dark side of personality at work. (30th August 2013) - Spain, Seth M.; Harms, Peter; LeBreton, James M.; Hodgkinson, Gerard P.; Ford, J. Kevin
Summary Although there has been increasing interest in dark personality traits in the organizational sciences, these characteristics remain relatively understudied and somewhat misunderstood. The present manuscript aims to clarify some of the issues surrounding dark personality traits by discussing the history of dark personality traits, how they relate to normal personality traits, their relative importance as determinants of organizational outcomes, and measurement issues surrounding the assessment of these characteristics. We will then discuss potential future directions for research investigating the causes and consequences of these traits as well as providing guidance on the implementation of dark personality assessment in the workplace for selection and training. Copyright © 2013 John Wiley & Sons, Ltd.